Decorating Cu2O with Copper Metal (Cu) through Facile Electrochemical Deposition for Methylene Blue Degradation - Noureen Zahra, Shyla; Firgie Wulandari; Muhammad Raihan Rauf; Arum, Ayuningsih (Chemistry and Materials, 2024)
A cuprous oxide (Cu2O) thin film was decorated with copper metal (Cu) using a simple electrochemical deposition method on a substrate of indium tin oxide at a potential of -0.3 V vs. Ag/AgCl and a temperature of 60 °C. This study aimed to investigate the role of Cu as a co-catalyst. The structure, phase, and morphology of Cu2O/Cu were characterized by X-ray diffraction, scanning electron microscopy, and energy-dispersive X-ray spectroscopy, respectively. The electrocatalytic performance of Cu2O/Cu was recorded using linear sweep voltammetry and electrochemical impedance spectroscopy techniques. The X-ray diffraction and scanning electron micrograph show that Cu was successfully deposited covering Cu2O. The current density of Cu2O/Cu increased by 2.70 mA/cm2 confirming the lower charge current resistance of 2.48 kΩ. The Cu-decorated Cu2O demonstrated an improved photocatalytic activity, as shown by increased MB degradation from 46.33% to 50.87%. It was believed from characterizations that Cu deposition leads to more dense carriers and charge transfer, hence higher photocatalytic activity towards MB degradation than bare Cu2O thin film.